A Cross-sectional Radiological Study of Ossification at Lower End of Ulna and Tip of Olecranon among Children and Adolescents coming to Forensic Medicine Department, Medical College, Kolkata, for Age Estimation - Chandan Bandyopadhyay 1 , Anamica Chakraborty2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: To study radiologically the ossification status of lower end of ulna and tip of olecranon andcompare with Galstaun chart and other standard charts.Material and Methods: A record based cross sectional study was performed in the department of Forensicand State Medicine, Medical College Kolkata for one month, on children and adolescent coming to thedepartment for age estimation over a span of past one year. Their chronological age was noted from birthcertificates. The X-Ray plates was looked for appearance and fusion of lower end of ulna and tip of olecranonand compared with Galstaun chart and other standard charts.Results: The records of 199 subjects (Male-142. Female-57) were examined, who belong to the age groupof 7yrs to 19yrs. After observing the appearance and fusion from X-Ray plates and comparing them withGalstaun chart it was seen that maximum deviation from mean age occurred in appearance of lower end ofulna. Appearance of tip of olecranon also had a wide deviation. Males were found to have more variationsthan females.